A Concise Route to MK-4482 (EIDD-2801) from Cytidine: Part 2 - Gopalsamuthiram, Vijayagopal; Williams, Corshai; Noble, Jeffrey; Jamison, Timothy F.; Gupton, B. Frank; Snead, David R. (Synlett, 2020)
A new route to MK-4482 was developed. The route replaces uridine with the more available and less expensive cytidine. Low-cost, simple reagents are used for the chemical transformations, and the yield is improved from 17% to 44%. A step is removed from the longest linear sequence, and these advancements are expected to expand access to MK-4482 should it become a viable drug substance.
Keywords: antiviral; nucleoside; COVID-19